A note on: Quasi-linear quotients and shellability of pure simplicial complexes. Issue 2 (1st February 2018) - Anwar, Imran; Shabbir, Khurram
ABSTRACT: The purpose of this note is to point out a careless error in the algebraic criterion of shellability of a pure simplicial complex Δ given in [1 ].